INFLUENCE OF MODERATION OF COMPANY STRATEGY ON CSR DISCLOSURES AND FINANCIAL PERFORMANCE MINING COMPANY IN INDONESIA - Budi Santoso Santoso (Universitas Pendidikan Ganesha, 2018)
This study aims to analyze the role of corporate strategy moderation in the influence of CSR performance on corporate financial performance. Company strategy is measured by Product Differentiation, CSR performance measured using Global Reporting Association (GRI) index, and financial performance measured with Return on Assets (ROA) period 2016-2017. Research population Mining companies listed in Indonesia Stock Exchange (BEI) in 2016 and 2017 and Companies that issue annual reports during the period 2016-2017. The results of this study indicate that the performance of CSR does not show significant influence to the company's financial performance and use the company's strategy as a moderator variable indicates that the company's strategy variable turns out to moderate significantly the impact of CSR performance on the financial performance of the company